Pengaruh penggunaan tongkat modifikasi terhadap keterampilan memukul bola kasti siswa - Irvan Zaenuri; Olivia Dwi Cahyani; Nurman Ramadhan (Physical Education Departement of University PGRI Jombang, 2026)
The purpose of this study is to ascertain how a modified stick can enhance rounders players' ball-hitting abilities among fifth-grade students at MI Islamiyah Tulungagung through the use of learning media in the form of a modified stick. Initial observations showed that most of the 30 students were still in the low category, with pretest scores ranging from 30 to 40. This study used a one-group pretest–posttest design and a quantitative methodology, in which the entire population was used as the sample through a total sampling technique, and the research instrument was a kasti ball hitting test, while the treatment was given over four sessions through stick swing exercises of 5 times × 2 repetitions and hitting balls at slow, medium, and fast speeds using a cricket bat. The results of the descriptive analysis showed an increase in the average score from 56.67 in the pretest to 64.33 in the posttest, with the score range changing from 30–40 to 80–90. The Shapiro–Wilk normality test proved that the data were normally distributed, with p = 0.090 for the pretest and p = 0.107 for the posttest, and the Paired Sample t-Test results showed a significant effect of using a cricket bat on improving kasti ball hitting ability, with t = –2.986, df = 29, and p = 0.006 (p < 0.05). This improvement indicates that modified teaching aids can help students improve strength, accuracy, and movement coordination when hitting the ball; nevertheless, the limited sample size and duration of the treatment are important notes, so future studies are recommended to involve a control group and a broader participant scope to strengthen the gen.